Determinants of credit rationing: a study of informal lenders and formal credit groups in Madagascar - Zeller, Manfred (International Food Policy Research Institute, 1994)
Previous research on the determinants of credit rationing exclusively focused on the behavior of formal lenders who contract directly with an individual borrower. Based on a household survey in Madagascar, this paper presents an analysis of credit rationing behavior by informal lenders and by members of community-based groups that allocate formal group loans among themselves. The results show that group members obtain and use locally available information about the applicant's creditworthiness in much the same way that informal lenders do. This paper therefore empirically confirms theoretical arguments made that community-based groups have an information advantage over distant formal bank agents.